What Went Wrong? Reflections on the Condition of Architecture and Urbanism in Lebanon - Haddad, Elie (2007)
In a short article presented at a conference in New York City two years ago, Joan Ockman lucidly diagnosed the contemporary dilemma faced by architecture, i.e. how to insert itself between a pessimistic discourse that warns of the end of time, and an uncritical surrender to globalization. This dilemma is now universal(i). It applies to New York City, where in the same context Kenneth Frampton commented on the dystopia of an “oddly paranoid, rather ruthless, instrumental and resentful landscape”(ii), as well as to other cities around the world, especially in the Third World, where more difficult conditions permeate architectural practice, resulting in even more devastated landscapes. This article will discuss issues that relate to architectural practice and pedagogy, drawing on specific examples in the context of Beirut, Lebanon, and reflecting on the impact of‘architectural education’ and the transformations within the architectural profession in this context. One can no longer deny the negative impact of economics on a profession that has been, for the most part, idealistic in its approach to the built environment, but the responsibility of architects and architectural education, can no longer beminimized in assessing the problems that cities like Beirut face today.